Elizabeth I in Writing Language, Power and Representation in Early Modern England (Queenship and Power, 2018)
This collection investigates Queen Elizabeth I as an accomplished writer in her own right as well as the subject of authors who celebrated her. With innovative essays from Brenda M. Hosington, Carole Levin, and other established and emerging experts, it reappraises Elizabeth's translations, letters, poems and prayers through a diverse range of approaches to textuality, from linguistic and philological to literary and cultural-historical. The book also considers Elizabeth as "authored," studying how she is reflected in the writing of her contemporaries and reconstructing a wider web of relations between the public and private use of language in early modern culture. Contributions from Carlo M. Bajetta, Guillaume Coatelen and Giovanni Iamartino bring the Queen's presence in early modern Italian literary culture to the fore. Together, these essays illuminate the Queen in writing, from the multifaceted linguistic and rhetorical strategies that she employed, to the texts inspired by her power and charisma.